Facile synthesis of novel activated carbons for the post-combustion capture of CO2 - Liu, Xin (2017)
The world faces unprecedented challenges in mitigating climate change and reducing CO2 emissions from fossil fuel utilisation has been clearly taken as one of the major climate change mitigation strategies. Among the carbon capture technologies, solid adsorbent looping technology (SALT) using activated carbon is considered to be one of the most promising methods due to the extensive sources raw materials, low price, high specific surface area and low energy requirement for regeneration. Synthesis of activated carbons with high adsorption capacity and CO2/N2 selectivity for post combustion capture (at a low CO2 partial pressure and high temperature) is the focus of current research on carbons. This project aims to utilize abundant and easy access materials such as biomass or polymers as precursors and alkaline metal based compounds as activating agents to prepare novel activated carbons with exceptional CO2 adsorption performance to meet the requirement of post combustion CO2 capture in power plants. Two kinds of precursors, biomass (rice husk) and polymer (polyisocyanurate foam), were employed to prepare effective activated carbons for post-combustion CO2 capture. A novel cost-effective methodology able to achieve the carbonization, chemical activation and simultaneous surface functionalization essentially in a one-step process were developed. The work on carbons derived from rice husk (RH) showed that the synthesised bio-carbons exhibit exceedingly high ultra-microporosity, accounting for up to 95% of total porosity. With a modest surface area of 1035 m2/g and a total pore volume of 0.43 cm3/g, the best performing RH carbon showed a record high and fully reversible CO2 uptake capacity of 2.0 mmol/g at 25 oC and a CO2 partial pressure of 0.15 bar, which was the highest uptake ever reported for bio-carbons. Furthermore, it was attempted to tablet precursors with different compacting pressures before activation in order to further improve the adsorption performance. The results showed that the compacted rice husk-derived carbons exhibited much higher ultra-microporosity, especially volume of pores smaller than 0.42 nm and a large amount of mesopores. This has led to exceedingly high CO2 uptake, up to 6.80 and 4.50 mmol/g at 0 and 25 °C respectively and 1 bar and 1.90 mmol/g at 25 °C and a CO2 partial pressure of 0.15 bar, which was much higher than samples prepared at 700 °C without compaction. Meanwhile, the compacted samples showed much higher initial slope (IS) CO2/N2 selectivity up to 170 at 25 °C while the selectivity of the sample prepared at 700°C without compaction was only 56. Polymer-derived carbons also showed exceedingly high levels of ultra-microporosity and unique surface chemistry for CO2 adsorption. The resulting ultra-microporous carbon foam achieved a record-high CO2 uptake of 2.12 mmol/g at 25 °C and 0.15 bar as well as a record-high CO2/N2 selectivity of 200, which is among the highest ever reported for porous carbon materials and most MOFs. In addition, the adsorption performance of samples at flue gas conditions (0.15 bar CO2 and 40-50 °C) were also studied. The samples showed record-high CO2 uptake of about 2 mmol/g at flue gas condition (40-50°C and 0.15 bar CO2), which was higher than any carbon materials from more sophisticated and cost-prohibitive methodologies, most zeolites and MOFs. The polymer-derived carbons investigated here exhibited fast adsorption kinetics and excellent stability and regenerability under simulated flue gas condition. Further studies in this project showed that the excellent performance of carbons from different precursors can be attributed to ultra-microporosity and favourable surface chemistry achieved by the facil one-step synthesis. The CO2 adsorption capacity is associated with the pore volume of pores smaller than a specific size, which varied with the temperature and partial pressure. The ultra-micropore volumes of pores smaller than 0.44 nm and 0.40 nm is responsible for the CO2 adsorption at 0.15 bar 25 °C and 50 °C respectively. In addition to ultra-micropores, this work showed that surface potassium groups on surface identified by EDX and XPS could significantly improve the CO2 adsorption performance, especially at low partial pressures. As for RH carbons, up to 50% of the total CO2 uptake was attributable to the unique surface chemistry, which appears to be dominated by the enhanced formation of extra-framework potassium cations, owing to the presence of zeolitic structures incorporated within the carbon matrices. The work on polymer derived carbons showed that there was a linear relationship existing between CO2 adsorption capacity and surface potassium content, while no direct relationship between nitrogen containing groups and CO2 adsorption capacity was observed. Meanwhile, the high heat of adsorption and IS selectivity also indicated the strong surface affinity to CO2. Overall, the prepared potassium doped carbons possess great potential as adsorbents for post combustion CO2 capture.